Potentiodyanmic corrosion behavior of Fe–18Cr–21Mn-0.65 N austenitic stainless steel exposed at 400–700 °C - Kumar S.; Jaiswal D.; Behera C.K.; Mahobia G.S. (My University, 2025)
Fe–18Cr–21Mn-0.65 N austenitic stainless steel was pre-exposed at intermediate temperature, from 400 to 700 °C, for different durations, up to 100 h. Corrosion behavior of the samples, unexposed as well as exposed, at different temperatures, was assessed in seawater (0.5 M NaCl) through potentiodynamic polarization. It was found to decrease with an increase in the temperature of exposure. Corrosion resistance of the passive layer formed, evaluated by EIS, showed that it decreased with increase in the temperature of exposure. The corroded samples were characterized by X-ray photoelectron spectroscopy (XPS) and Scanning electron microscopy (SEM-EDS). XPS analysis revealed the presence of oxides and hydroxide of Cr+3, Mn+3, and Fe+3. The pitting mechanism was prominent in the specimens exposed from room temperature to 500 °C, whereas a mixed-mode of corrosion (intergranular combined with accelerated pitting) was there in the samples exposed at higher temperatures of 600 and 700 °C. Precipitation of Cr2N along grain boundaries and within the matrix was the leading cause of the deterioration in the corrosion resistance. © 2022 Elsevier B.V.